Importance of pharmacogenetics in the treatment of children with attention deficit hyperactive disorder: a case report - Tan-kam T; Suthisisang C; Pavasuthipaisit C; Limsila P; Puangpetch A; Sukasem C (Dove Medical Press, 2013)
Teerarat Tan-kam,1 Chutamanee Suthisisang,2 Chosita Pavasuthipaisit,1 Penkhae Limsila,1 Apichaya Puangpetch,3 Chonlaphat Sukasem31Yuwaprasart Waithayopathum Child and Adolescent Psychiatric Hospital, Department of Mental Health Services, Ministry of Public Health, 2Department of Pharmacology, Faculty of Pharmacy, Mahidol University, 3Division of Pharmacogenomics and Personalized Medicine, Department of Pathology, Faculty of Medicine, Ramathibodi Hospital, Mahidol University, Bangkok, ThailandAbstract: This case report highlights the importance of pharmacogenetic testing in the treatment of attention deficit hyperactive disorder (ADHD). A 6-year-old boy diagnosed with ADHD was prescribed methylphenidate 5 mg twice daily (7 am and noon) and the family was compliant with administration of this medication. On the first day of treatment, the patient had an adverse reaction, becoming disobedient, more mischievous, erratic, resistant to discipline, would not go to sleep until midnight, and had a poor appetite. The All-In-One PGX (All-In-One Pharmacogenetics for Antipsychotics test for CYP2D6, CYP2C19, and CYP2C9) was performed using microarray-based and real-time polymerase chain reaction techniques. The genotype of our patient was identified to be CYP2D6*2/*10, with isoforms of the enzyme consistent with a predicted cytochrome P450 2D6 intermediate metabolizer phenotype. Consequently, the physician adjusted the methylphenidate dose to 2.5 mg once daily in the morning. At this dosage, the patient had a good response without any further adverse reactions. Pharmacogenetic testing should be included in the management plan for ADHD. In this case, cooperation between the medical team and the patients' relatives was key to successful treatment.Keywords: attention deficit hyperactive disorder, pharmacogenomics, CYP2D6, adverse drug reactions, dose adjustment, intermediate metabolizer